What the Past Tells About the Future: Historical Prices in the Durable Goods Market - Gong, Zheng; Huang, Jin; Chen, Yuxin (Management Science, 2022)
We investigate how historical price information (e.g., accessed through price trackers) influences consumers’ purchase decisions and thus affects a firm’s dynamic pricing strategy. We first show that when consumers with heterogeneous tastes are not informed about historical prices, the monopolist charges a high regular price for most of the time and periodically holds low-price sales. Then we consider the case in which a small fraction of consumers (such as price tracker users) become informed of historical prices. At the new equilibrium, the monopolist lowers the regular price and advances sales, implying shorter price cycles, more frequent sales, and a positive spillover effect of price tracker users’ informational advantage on the rest of uninformed consumers. We conclude with a discussion of the impact of price trackers on firms and other relevant managerial implications of the model. This paper was accepted by Dmitri Kuksov, marketing. Funding: Y. Chen thanks the National Science Foundation of China [Grant 71972043] for the support. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4309 .